Sustainable Land Management : Challenges, Opportunities, and Trade-offs - World Bank (Washington, DC: Wolrd Bank, 2012)
Land is the integrating component of all livelihoods depending on farm, forest, rangeland, or water (rivers, lakes, coastal marine) habitats. Due to varying political, social, and economic factors, the heavy use of natural resources to supply a rapidly growing global population and economy has resulted in the unintended mismanagement and degradation of land and ecosystems. This book provides strategic focus to the implementation of sustainable land management (SLM) components of the World Bank's development strategies. Sustainable land management is a knowledge-based procedure that integrates land, water, biodiversity, and environmental management to meet rising food and fiber demands while sustaining livelihoods and the environment. This book articulates priorities for investment in sustainable land management and natural resource management and identifies the policy, institutional, and incentive reform options that will accelerate the adoption of productivity improvements and pro-poor growth with sustainable land management.